Google Sheet Based Air Dryer Compressor Monitoring System: Sistem Pemantauan Kompresor Pengering Udara Berbasis Google Sheets - Muhammad Irwani Amin; Arief Wisaksono (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Compressed air systems require moisture control to maintain reliable operation and protect pneumatic equipment from damage caused by water vapor. Specific Background: Air dryer compressors equipped with evaporator systems are commonly used to reduce humidity in compressed air, while real-time monitoring is needed to observe operating conditions such as temperature, humidity, and pressure. Knowledge Gap: Conventional monitoring approaches often provide limited accessibility and do not integrate operational data into a cloud-based platform for continuous observation and data storage. Aims: This study aimed to design and develop an air dryer compressor with an evaporator system integrated with Google Sheet-based monitoring using Internet of Things technology. Results: The developed system employed DHT22 and pressure transmitter sensors connected to an ESP32 microcontroller to measure temperature, humidity, and air pressure, with data transmitted and displayed in Google Sheet in real time. Sensor testing showed close agreement with standard measuring instruments, while the monitoring platform continuously recorded operational parameters and generated organized data records. Novelty: The study presents the integration of an evaporator-based air dryer compressor with IoT-enabled monitoring and cloud-based data logging through Google Sheet within a single operational system. Implications: The proposed system provides accessible remote monitoring, structured data management, and continuous observation of compressor operating conditions, supporting reliable pneumatic system operation and maintenance activities.Highlights: Real-time data transmission enabled continuous observation of temperature, humidity, and air pressure parameters. DHT22 measurements showed close agreement with reference instrument readings during testing. Cloud-based records provided organized storage and remote access to operational information. Keywords: Air Dryer Compressor; Internet of Things; ESP32; Google Sheet Monitoring; Pressure Transmitter